Stochastic inflation: scaling solution for N fields - Amendola, Luca (Classical and quantum gravity, 1993)
The Fokker-Planck equation for the primordial inflationary fluctuations is solved in the scaling approximation, when the classical drift dominates over the quantum diffusion. The scaling procedure is generalized to the case in which several fields are involved. The conditions imposed on the Kramers-Moyal coefficients in order to derive the scaling variables turn out to be fulfilled in some simple multi-field case. An analytical solution in the case of a two-field inflationary model is worked out.
Gesehen am 21.11.2017